Pengaruh Aplikasi Arang Sekam Dan Pupuk Majemuk Tabur Terhadap Pertumbuhan Dan Rroduksi Tanaman Tomat (Lycopericum esculentum Mill. ) - Lentina Sitinjak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
Abstract Good agricultural practices are necessary for increasing of crop production. This study aimed to determine the effect of husk rice charcoal and compound fertilizer on tomato growth and yield production. Husk rice charcoal was added using three levels including 0, 100, and 200 g/plant. Beside, compound fertilizer was added to media of plants with three levels including 0, 2, and 6 g/plant. The treatments were arranged in a randomized completely block design of which each treatment was made in three replicates. The results showed that application of 100 and 200 g husk charcoal/plant increased tomato growth and production of 60 to 110 g / plant and 15 to 30% respectively. In contrast, plant height at the age of 2 WAP, the application of compound fertilizer did not significantly affect yield production and plant height except plant height at 2 WAP. No interaction of the two treatments was found on plant growth and yield production.